Peripheral nerve sheath tumors – case series in tertiary health care center in the central India - Sarika More,; Madhubala Swarnakar,; Rajendra Kumar Chandrakar,; Sujata Singh, (Asian Journal of Medical Sciences, 2022)
Peripheral nerve sheath tumors (PNST) are one of the most common neoplasms, with classical morphology and histopathological features, but they can be diagnostically challenging at times. Albeit well defined subtypes of PNST have been described in literature, but controversies regarding reporting and typing of these tumors persists. Malignant PNSTs represent a diagnostically challenging group. Although the diagnosis and classification of most PNST are relatively straightforward, borderline grey zone neoplasms continue to be a diagnostic difficulty. In our case series, we attempt in providing some useful information for the oncopathologist to help navigate these persistent and challenging problems. In the present study, we found 26 cases of PNST, out of which the most common was schwannoma (n=18), followed by neurofibroma (n=7) and one case of malignant type, that is, malignant PNST. The cases involving all age from 12 to 65 years, showing slight male preponderance.